1986
DOI: 10.1071/ph860433
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of Pulsar Radiation and Electron Density Turbulence in the Interstellar Medium

Abstract: We report measurements, using the Culgoora circular array at 80 and 160 MHz and the Parkes 64 m telescope at 410 MHz, of the pulse broadening due to interstellar scattering on 33 pulsars. These results are added to published data on 52 other pulsars in order to investigate the interstellar turbulence levels over 85 paths in the Galaxy. We find a significant relation between the turbulence level C~ and dispersion measure, heliocentric distance, galactocentric distance, galactic latitude and galactic longitude. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 4 publications
3
31
1
Order By: Relevance
“…Two similar τ measurements at 160 MHz were obtained by Alurkar et al (1986) and Slee et al (1980) using the Culgoora circular array, namely 26.5 ± 8.1 and 27 ± 7 ms (Table 2). At 163.5 MHz, we obtain 30.7 ± 1.9 ms, within their estimated error at 160 MHz.…”
Section: Psr J0040+5716supporting
confidence: 80%
See 2 more Smart Citations
“…Two similar τ measurements at 160 MHz were obtained by Alurkar et al (1986) and Slee et al (1980) using the Culgoora circular array, namely 26.5 ± 8.1 and 27 ± 7 ms (Table 2). At 163.5 MHz, we obtain 30.7 ± 1.9 ms, within their estimated error at 160 MHz.…”
Section: Psr J0040+5716supporting
confidence: 80%
“…This value is in good agreement with the values obtained by Löhmer et al (2004), α = 3.4 ± 0.2, and L15b, α = 3.35 +0.36 −0.41 . Both these literature values of α are determined using other published scattering measurements between 110 and 250 MHz (Rickett 1977;Slee et al 1980;Alurkar et al 1986;Löhmer et al 2001;Kuzmin & Losovsky 2007), and therefore serve as an independent check of our measurements. Our AM leads to α = 3.9 ± 0.5, in agreement with theoretical values of 4 or 4.4.…”
Section: Psr J0040+5716mentioning
confidence: 76%
See 1 more Smart Citation
“…At frequencies of a few GHz the pulse profile is dominated by a single component. At frequencies below about 400 MHz, profile broadening due to interstellar scattering is evident (Alurkar et al 1986). Fig.…”
Section: Psr J1721−3532 (B1718−35)mentioning
confidence: 99%
“…Studies of pulsar scintillation (Arlurkar et al, 1986) and radio sources broadening (Rao and Slee, 1988) have shown that turbulence in the ionized interstellar medium increases towards the galactic plane and towards the galactic centre. Therefore it is reasonable to expect a dependence of source variability on galactic co-ordinates if propagation effects in the interstellar medium take place.…”
Section: Introductionmentioning
confidence: 99%